2017
DOI: 10.1186/s13287-017-0573-7
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of FGF receptor 1 activity mediates sorafenib antiproliferative effects in human malignant pleural mesothelioma tumor-initiating cells

Abstract: BackgroundMalignant pleural mesothelioma is an aggressive cancer, characterized by rapid progression and high mortality. Persistence of tumor-initiating cells (TICs, or cancer stem cells) after cytotoxic drug treatment is responsible for tumor relapse, and represents one of the main reasons for the poor prognosis of mesothelioma. In fact, identification of the molecules affecting TIC viability is still a significant challenge.MethodsTIC-enriched cultures were obtained from 10 human malignant pleural mesothelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…We thus used an in vitro kinase assay to examine the effects of Jzu 17, sunitinib, and sorafenib on the intrinsic TK activity of VEGFR‐2. Sunitinib (Latham et al, ) and sorafenib (Pattarozzi et al, ) are inhibitors of many RTKs, which also suppress the kinase activity of bFGFR. The effects of these compounds on bFGFR1 kinase activity were also determined.…”
Section: Resultsmentioning
confidence: 99%
“…We thus used an in vitro kinase assay to examine the effects of Jzu 17, sunitinib, and sorafenib on the intrinsic TK activity of VEGFR‐2. Sunitinib (Latham et al, ) and sorafenib (Pattarozzi et al, ) are inhibitors of many RTKs, which also suppress the kinase activity of bFGFR. The effects of these compounds on bFGFR1 kinase activity were also determined.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple members of the miR-15/16 family may be targeted with microRNA mimics, whereas FGFRs and Bcl-2 have the advantage of being druggable. FGFR inhibition has shown promising effects in various preclinical studies (Dey et al, 2010;Maruyama-Takahashi et al, 2008;Metzner et al, 2011;Pattarozzi et al, 2017;Qing et al, 2009;Schelch et al, 2014) and is currently being tested in patients with solid tumors, especially in those with known FGFR overexpression or genomic alterations ( Katoh and Nakagama, 2014). In mesothelioma, a phase lll study using the multi-RTK inhibitor nintedanib (NCT01907100) and a phase lb trial using the FGFR ligand trap GSK3052230 in combination with first-line chemotherapy (NCT01868022) are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies on CSC from glioblastoma, breast cancer or osteosarcoma (119,(121)(122)(123), demonstrated a higher sensitivity of this subpopulation to metformin, as compared to "differentiated" tumor cells, determining the development of a drug repositioning approach (124,125). In particular, while it is well-accepted that stem-like cells are particularly resistant to classical cytotoxic drugs due to the overexpression of drug-extruding pumps and DNA-repairing enzymes (110), in CSC cultures from different tumors the sensitivity to molecular-targeted drugs, in particular to tyrosine kinase inhibitors, is retained (114,126).…”
Section: Drug Sensitivity Of Pituitary Adenoma Stem Cellsmentioning
confidence: 99%